2019
DOI: 10.1088/1742-6596/1374/1/012029
|View full text |Cite
|
Sign up to set email alerts
|

The preventive effect of activated charcoal on HDL levels and aorta histopathological profiles in hypercholesterol rat models

Abstract: Hypercholesterolemia is a condition which the cholesterol levels in the blood exceeds the normal value. The use of hypercholesterolemia drugs or synthetic drugs in a long term will cause severe side effects. Therefore, it is important to explore an alternative preventive agent of hypercholesterolemia derived from natural materials, such as activated charcoal. The activated charcoal can absorb substances thousands times of its own weight and might be an effective and non-toxic material. The research aimed to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…The significant differences noticed in the weights of the heart in relation to live weight of the supplemented group can be attributed to the lowering effect of AC on serum cholesterol levels which may be responsible for the increased activity and weights of the heart. Activated charcoal interferes with the entero-hepatic circulation of bile acid and cholesterol, thereby lowering serum cholesterol in cases of hypercholesterolemia [90,91]. In a related development, Shabani et al [92] and Dim et al [26] reported that plasma cholesterol levels were reduced in birds whose diets were supplemented with activated charcoal.…”
Section: Studymentioning
confidence: 99%
See 4 more Smart Citations
“…The significant differences noticed in the weights of the heart in relation to live weight of the supplemented group can be attributed to the lowering effect of AC on serum cholesterol levels which may be responsible for the increased activity and weights of the heart. Activated charcoal interferes with the entero-hepatic circulation of bile acid and cholesterol, thereby lowering serum cholesterol in cases of hypercholesterolemia [90,91]. In a related development, Shabani et al [92] and Dim et al [26] reported that plasma cholesterol levels were reduced in birds whose diets were supplemented with activated charcoal.…”
Section: Studymentioning
confidence: 99%
“…These reductions in serum cholesterol levels have elucidated the fact that activated charcoal could be useful in the treatment of hypercholesterolemia [90,91]. This is achieved by its interference on entero-hepatic circulation by binding to cholesterol and cholesterol-containing bile acids in the gut, thus preventing them from being absorbed [99].…”
Section: Studymentioning
confidence: 99%
See 3 more Smart Citations